PERSETUJUAN TINDAKAN KEDOKTERAN PADA TINDAKAN BEDAH DITINJAU BERDASARKAN PERATURAN MENTERI KESEHATAN REPUBLIK INDONESIA NOMOR 290 TAHUN 2008 TENTANG PERSETUJUAN TINDAKAN KEDOKTERAN DI RUMAH SAKIT UMUM DAERAH PETALA BUMI PROVINSI RIAU - JIMMY FEBRYANTO SILITONGA; Mardalena Hanifah; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Doctor, patient and hospital are the law subject in medical care. Medical care begins with therapeutic transaction. It means an agreement between doctor and patient based on faith. Doctor and patient has right and duty their self. Doctor as a professional health care providers must be know and do the sixteen duty in their profession, which one consist from informed consent. Informed consent must be explained clearly. But in the fact, the doctor seldom expplained about informed consent, that may caused patient never know abaout it.In this case, related to implementation and responsibility in medical care especially surgery at RSUD Petala Bumi Provinsi Riau. The purpose of this thesis, First, the implementation of informed consent in surgery at RSUD Petala Bumi Provinsi Riau. Second, the responsibility of medical care for patient based on informed consent in surgery at RSUD Petala Bumi Provinsi Riau. The type of this research be classified as sociological juridical research, because in this research, the author directly organize a research in the location of research to give a complete describing about the issues that was examined. This research be held in RSUD Petala Bumi Provinsi Riau, whereas the population and sample is a whole party that was related to the issues. The data based on primary data, secondary data, the collecting data technical in this research consist of quitionaire, interview and library research.There are two main idea that can be resumed. First, the implementation of informed consent in RSUD Petala Bumi Provinsi Riau was not working. The information that given by doctor was not completely. In fact, the informed consent form was not fill too completely. The second, RSUD Petala Bumi Provinsi Riau does not have the list of medical record about informed consent. It means RSUD Petala Bumi Provinsi Riau does not care about the responsibility in medical care to the patient. The conslusion is the implementation of informed consent just only formality without caring the law aspect. The author suggestion, First, for the government through Health Ministry must make a rule of law to the health care providers and the doctor that was not make informed consent in their medical care. The second, doctor as a part in medical care that directly communicate to the patient must fix the relationship both of them. RSUD Petala Bumi Provinsi Riau must too make the list of medical record about informed consent.Keywords: Informed Consent, Surgery, Therapeutic